Students’ Self-Assessment on Fluid Statics Concept Understanding in Physics Learning - Sri Agustini (Physics Education, 2026)
This study investigates students’ self-assessment of their understanding of fluid statics concepts in physics education. Using a descriptive survey approach, data were collected from 63 respondents using a 25-item self-assessment instrument based on a 4-point Likert scale ranging from 1 (unable) to 4 (very able). The instrument covered conceptual understanding, computational skills, and practical application of fluid statics topics, including hydrostatic pressure, Archimedes’ law, Pascal’s law, viscosity, and real-world applications. Results revealed that the majority of students rated themselves at level 3 (sufficiently able), indicating adequate theoretical understanding but limited confidence in practical applications. The most challenging areas were vacuum pump applications (38.1% at level 2), connections to natural phenomena (34.9% at level 2), and hydraulic machine pressure (34.9% at level 2). The highest self-assessed competencies were found in fluid density analysis and experimental density calculations, each with 68.3% at level 3. These findings indicate that while students possess adequate conceptual knowledge of fluid statics, targeted instructional interventions emphasizing practical applications and hands-on laboratory activities are needed to bridge the theory-practice gap in physics learning.